Multi-functional vesicles improve Helicobacter pylori eradication by a comprehensive strategy based on complex pathological microenvironment - Xiaonan Chen; Yiqing Zou; Shuqi Zhang; Pengchao Fang; Shuxuan Li; Pengyu Li; Yingying Sun; Gang Yuan; Haiyan Hu (Elsevier, 2022)
Helicobacter pylori (H. pylori), creating a global infection rate over 50%, presents great challenges in clinical therapies due to its complex pathological microenvironment in vivo. To improve the eradication efficacy, herein we fabricated a pharmaceutical vesicle RHL/Cl-Ch-cal where cholesterol-PEG, calcitriol and first-line antibiotic clarithromycin were co-loaded in the rhamnolipid-composed outer lipid layer. RHL/Cl-Ch-cal could quickly penetrate through gastric mucus layer to reach H. pylori infection sites, and then effectively destroyed the architecture of H. pylori biofilms, killed dispersed H. pylori and inhibited the re-adhesion of residual bacteria (called biofilms eradication tetralogy). Moreover, RHL/Cl-Ch-cal activated the host immune response to H. pylori by replenishing cholesterol to repair lipid raft on the cell membrane of host epithelial cells. Finally, RHL/Cl-Ch-cal killed the intracellular H. pylori through recovering the lysosomal acidification and assisting degradation. In experiments, RHL/Cl-Ch-cal demonstrated prominent anti-H. pylori efficacy in the classical H. pylori-infected mice model. Therefore, the study provides a "comprehensive attack" strategy for anti-H. pylori therapies including biofilms eradication tetralogy, immune activation and intracellular bacteria killing.